2012
DOI: 10.2118/157852-pa
|View full text |Cite
|
Sign up to set email alerts
|

How To Assess a Depth of Permeability Impairment of the Wellbore Zone Using Drillstem-Testing Flow-Period Data

Abstract: This paper provides a simple procedure for evaluation of depth of permeability impairment within the wellbore zone using drillstem-testing (DST) flow-period data. Also computed are skin factor, permeability of the wellbore zone, and permeability of the reservoir. Contrary to the type-curve-fitting method, straight-line approximations were used to compute these values. All calculations presented are for "real-world" data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…where N -number of log p D vs. t i data which plot along the straight line. As shown in [12] the INiG -PIB method may be also used for the calculation of the wellbore zone permeability and the extent of the zone with improved/impaired permeability around the wellbore. It has been demonstrated in paper [11] that the INiG -PIB method yields results which are very close to the results of "slug test" method.…”
Section: Methods Of Interpretation Of "Slug Test" Data Using Inig -Pibmentioning
confidence: 99%
See 1 more Smart Citation
“…where N -number of log p D vs. t i data which plot along the straight line. As shown in [12] the INiG -PIB method may be also used for the calculation of the wellbore zone permeability and the extent of the zone with improved/impaired permeability around the wellbore. It has been demonstrated in paper [11] that the INiG -PIB method yields results which are very close to the results of "slug test" method.…”
Section: Methods Of Interpretation Of "Slug Test" Data Using Inig -Pibmentioning
confidence: 99%
“…As demonstrated in [12] the short time data in Figure 3 represents the wellbore zone permeability (fracture permeability), whereas the long time data indicates permeability of coal matrix. If so, the following values may be calculated for the above provided example using the INiG -PIB method: As shown, the results of the slug test and the INiG -PIB method are in acceptable agreement.…”
Section: Methods Of Interpretation Of "Slug Test" Data Using Inig -Pibmentioning
confidence: 99%
“…For nearly all of the analyzed case studies it has been observed that the log p D vs. t plot is linear for the initial and final period of flow and that both flow periods are separated by a transition period, for which the log p D vs. t relation does not follow the linear trend (Szpunar and Budak, 2012). This observation may be explained by the difference between the permeability of the well bore zone and permeability of the reservoir using the following reasoning:…”
Section: Technique For Interpretation Of Dst Flow Period Datamentioning
confidence: 98%